Peranan Sekretaris dalam Memanfaatkan Teknologi Perkantoran Guna Meningkatan Efisiensi Kerja di PERUM Perhutani Unit III Jawa Barat & Banten Kesatuan Pemangkuan Hutan (KPH) Bandung Utara - Azizah, Nur (Universitas Pahlawan Tuanku Tambusai, 2024)
The increasingly rapid development of the times and technology means that a secretary is required to be able to work quickly and efficiently. In carrying out his duties, especially administrative tasks, the use of office technology is very necessary for a secretary. The use of office technology provides great benefits for the secretary of Perum Perhutani KPH BDU to work efficiently. The research method used is a qualitative descriptive research method, namely a method that describes problem solving based on accurate facts and current reality and then these problems are analyzed based on the data collected. The data collection techniques used were observation, interviews, literature study and document study. The purpose of this research is to find out to what extent the role and duties as a secretary in utilizing office technology at Perum Perhutani KPH BDU are good enough so that work efficiency increases.